Implementación de un biodigestor para la producción de biogás - Quelal Chugá, Kevin Alejandro (2019)
Ecuador is a country where agriculture and new technologies grow, as well as pollution and global warming due to the growth of industrial production, for this reason, it allows finding means of solution for these purposes, there are areas in the country that are increasing and devoted to agriculture, with the production of milk from cattle and both one of the sources that cause global warming due to animal waste. This project is focused on providing a solution to the pollution problem generated by the cattle excreta, from the biochemical anaerobic treatment implementing a biodigestion system, generating mainly methane (CH4) which is a renewable energy element that replaces LPG gas, even being applied for power generation. The biodigestor implementation to produce biogas was carried out and used as thermal energy for food cooking or lighting, as secondary products of biodigestion is obtained biofertilizer and biosun. Each of the parts that make up the biodigestion system was measure and implemented appropriately attaching to the process. The daily production of biogas was approximately 3.82 m3/day, relate in terms of volume 1 m3 of biogas representing 0.5 kg of LPG gas, in terms of the calorific power of the biogas relative to LPG it was concluded that food cooking requires more time, so a force must be exerted on the gasometer to maintain constant pressure. Taking advantage of this alternative energy source such as biomass, pollution in the farm was reduced and LPG gas consumption costs and the use of chemical fertilizers were reduced.